Bait and habitat preferences, and temporal variability of social wasps (Hymenoptera: Vespidae) attracted to vertebrate carrion - Moretti, Thiago de Carvalho [UNESP]; Giannotti, Edilberto [UNESP]; Thyssen, Patrícia Jacqueline; Solis, Daniel Russ [UNESP]; Godoy, Wesley Augusto Conde (Oxford University Press (OUP), 2011)
In addition to feeding on carrion tissues and fluids, social wasps can also prey on immature and adult carrion flies, thereby reducing their populations and retarding the decomposition process of carcasses. In this study, we report on the occurrence and behavior of social wasps attracted to vertebrate carrion. The collections were made monthly from September 2006 to October 2007 in three environments (rural, urban, and forest) in six municipalities of southeast Brazil, using baited bottle traps. We collected Agelaia pallipes (Olivier, 1791) (n = 143), Agelaia vicina (Saussure, 1854) (n = 106), Agelaia multipicta (Haliday, 1836) (n = 18), and Polybia paulista Ihering, 1896 (n = 3). The wasps were observed feeding directly on the baits and preying on adult insects collected in the traps. Bait and habitat associations, temporal variability of social wasps, and possible forensic implications of their actions are discussed. © 2011 Entomological Society of America.
Keywords: Agelaia; Epiponini; forensic entomology; necrophagy; Polybia; animal; biodiversity; Brazil; classification; ecosystem; fly; food chain; food preference; forensic pathology; physiology; population dynamics; season; vertebrate; wasp; Animals; Biodiversity; Diptera; Ecosystem; Food Chain; Food Preferences; Forensic Pathology; Population Dynamics; Seasons; Vertebrates; Wasps; Agelaia multipicta; Agelaia pallipes; Hexapoda; Hymenoptera; Polybia paulista; Vertebrata; Vespidae